Delineamentos da responsabilidade penal individual na direção de empresas - Servidoni, André Renato (2006)
Penal law had a great evolution with the years.First basedon the objective responsibility, it did without the guilt to punish the criminal agent. However, this responsibility was not consistent and therefore, it starts the subjective responsibility study, present in our legislation currently, including the constitional sphere. Therefore, the purpose of this work was to broach the guilt evolution, first through the foreign doctrine legislation connotation. This study is important for the lawsuit under process conclusion, mainly in the cases wich the responsible for companies punishment when they are charged with some penal lawsuit because the judicial power, disenses the study about the guilt of each agent in some opportunities attributing the responsibility for them in a widespread way, injuring the culpability principle. Anyway, through the doctrine study, legislation and jurisprudence, it was said the culpability principle must be respected and applied under to break the law of many principles, among them the sentence individuality and objective responsibility